MEMORY EXERCISES TO IMPROVE SHORT-TERM MEMORY IN MENINGIOMA PATIENTS: CASE REPORT - May Maria Magdalena Worabay; Agis Taufik; Arif Setyo Upoyo (International Journal of Biomedical Nursing Review, 2024)
Introduction: Meningiomas are a type of brain tumor that develops from the meninges (lining of the brain, that is, the membranes surrounding the brain and spinal cord. Another problem that occurs due to meningiomas and very often occurs is memory impairment. This nursing care is given with the aim of reducing memory impairment in meningioma sufferers with improved memory. Purpose: To determine the effect of the application of short-term memory exercises on memory impairment in meningioma patients. Result: The patient has been stiff for 1 month, speaks indirectly, often barks, irritability and headaches such as pulling. Results of MCT-Scan Head examination with contrast, effect: Vasogenic edema extensive in the bilateral frontotemporoparietal lobe, no picture of enhancing mass. Blood pressure: 109/65mmHg. Pulse; 90x/min, Temperature; 36.2oC, Respiration; 20x/min, SpO2; 99%, Weight; 53kg, Height; 150cm. Conclusion: The implementation of nursing given to Mrs. S with Chordoid Meningioma obtained very significant results in improving short-term memory and decreasing acute pain after being given memory training interventions and deep breath relaxation. Improvement in short -term memory has begun to be seen at the first intervention as well as acute pain reduced from 6 to 4.